MODEL PENYELESAIAN KONFLIK DI LEMBAGA ADAT - Kamaruddin Kamaruddin (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2013)
So far, there is a claim that the conflict resolution conducted by tradition institution is mediation, but in some extend it showed the differences in principle and procedure. Based on the argument this article has the purposes to know any conflict frequently broken among Aceh community, the patterns of cooperation of the tradition institutions, and to know the most dominant institution in resolving conflict. Applying qualitative method, it is revealed that tradition institutions took a very important part in resolving confling in Aceh society. Eventhough all elements of the tradition institutions are involved in conflict resolution but in the processes of conflict resolution in gampong level, keuchik has a very important and strategic role.